Effect of corona discharge on cadmium sulphide and lead sulphide films. (4th March 2018) - Koul Chaku, Anemone; Singh, Pramod K; Bhattacharya, Bhaskar
ABSTRACT: This paper describes the effect of corona discharge on cadmium sulphide (CdS) and lead sulphide (PbS) films prepared using the chemical route. The property of films before and after exposure to corona has been described in detail. The electronic properties of the CdS and PbS films have been studied by current-voltage (I-V), capacitance-voltage (C-V) measurements. The structural properties and surface morphology were studied by using X-ray diffraction and scanning electron microscopy before and after exposing to Corona discharge. The films displayed the change in surface morphology after exposure to the corona discharge. It has been found that the films showed an increase in resistivity after exposure. This change in property has been attributed to modification in surface states. Time-dependent recovery indicated that room temperature annealing is sufficient to regain the normal resistivity of the films. The experiment was carried with the aim of studying the effect of the interaction of corona discharge on the semiconductor films and its subsequent effects.